Association Between Diabetic Control And Anti-Diabetic Medication Adherence Using 8-Point Morisky Medication Adherence Scale In Local Population Of Khyber Pakhtunkhwa - Siddiqi, Fuad Ahmad; Saeed, Bilal; Hussain, Mehmood; Anwar, Wasif; Riaz, Sidra; Abbas, Naveed (Journal of Rawalpindi Medical College, 2023)
Abstract: Background: Drug adherence to medications in diabetes is very necessary for strict glycemic control. Many factors in diabetics are associated with low adherence to drugs resulting in complications. Methods: This research was conducted as an observational study with cross-sectional study design. It was scheduled between July 2022 to December 2022 in medical outpatient department of Combined Military Hospital, Peshawar Results: 115 individuals were inducted over a period of 6 months from medical OPD ex Combined Military Hospital Peshawar. Five patients failed to follow-up with research team resulting in a total of 110 participants included in results. Average age across the study sample was 50.25 ± 11.97 years with 58 (52.73%) males and 52 (47.27%) females. Most participant in our study sample were educated up to matriculation with BMI <25kg/m2. Average duration of diabetes across the sample was 6.1 ± 3.69 years. In treatment options, 53 (48.18%) individuals were only managed with oral therapy, 16 (14.55%) on insulin only while 41 (37.27%) were prescribed with both oral hypoglycemic drugs and insulin. Most common comorbid across study population was hypertension, seen in 59 (53.94%) diabetic patients, followed by cataract in 41 (37.47%) and IHD in 33 (30%) patients. In all 110 individuals, only 29 (26.36%) individuals had good glycemic control i.e., HbA1c <7% with average glycosylated hemoglobin percentage measuring 8.29% ± 1.59%. As per MMAS-8 score, 25 (22.73%) patients reported good adherence, 31 (28.18%) patients reported fair adherence while rest 54 (49.09%) were found to have bad adherence. Average MMAS-8 score was 5.17. Conclusion: There is a correlation between medication adherence as measured by MMAS-8 score with control of diabetes as measured by HbA1c score in the range of 1.824% across the range of MMAS-8 score from 0-8. Sleep quality, BMI and multiple comorbid conditions were also linked with raised HbA1c. Key words: Drug adherence, Morisky Medication Adherence Scale, Diabetes, Non-diabetes, diabetic medications